Double Emulsion Based Alginate/Chitosan Prepared by Ultrasound for Bioactive Encapsulation - Prasetyaningrum, Aji; Ashianti, Aulia Dwi; Rokhati, Nur; Setyaningsih, Yuliani (BRIN Publishing (Penerbit BRIN), 2025)
Water-in-oil-in-water (W/O/W) emulsion is an effective technology for encapsulating bioactivity but has poor stability. This study aims to evaluate the effect of ultrasonication on the preparation of double emulsions with varying alginate/chitosan ratios (1:1, 1:2, 2:1) and sonication times between 0 and 7 minutes. The results showed that a sonication time of 7 minutes resulted in the best storage stability (0.00–1.02%) and thermal stability (17.13–23.21%), a significant decrease in droplet size (2.08–2.87 μm), and higher emulsion activity index (EAI) (16.11–38.10 m2/g) and emulsion stability index (ESI) (63.28–89.74 min) values. The alginate/chitosan ratio of 2:1 also gave the most optimal results with storage stability of 4.58%, thermal stability of 36.23%, droplet size of 2.08–4.14 μm, and EAI and ESI values of 16.12 m2/g and 48.42 min. The ultrasonic-assisted alginate/chitosan double emulsion method effectively improved the stability and bioavailability of bioactive and presents significant potential for food and pharmaceutical applications.